Acral peeling syndrome/Epidermolysis bullosa simplex. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Acral peeling syndrome and epidermolysis bullosa simplex present since the first months very similar blisters and scaling of the hands and feet that therefore require a differential diagnosis.